"Multiplex est modus": elements of accommodation in the early Jesuit missions to India, 1545-1575 - Blankemeyer, BT (2020)
My project explores the methodologies of missionaries of the Society of Jesus in southern India between Francis Xavier's arrival in 1542 and the policy reforms under Alessandro Valignano in 1575, investigating the presence of cultural accommodation within the attitudes and decisions of various Jesuits. During the three decades between the Society’s foundation and Valignano’s arrival in India, Jesuits faced a number of issues both internally and externally, suggesting an organization prone to the influences of various individuals and contemporary ecclesiastical and secular politics. I argue that these factors presented limits to the development of more adaptive techniques which characterised cultural accommodation of the late sixteenth and early seventeenth century through Matteo Ricci and Roberto de Nobili, and that analysing these can help illustrate why such a policy did not manifest during earlier decades.